KARAKTER ELEMEN PENGUAT FASAD COFFEE SHOP : STUDI KASUS DI JALAN SEPAKAT 2 KOTA PONTIANAK - Zairin Zain; Thoriq Pratama (NALARs, 2026)
The rapid growth of coffee shop businesses in urban areas such as Jalan Sepakat 2, Pontianak, highlights a significant shift in commercial space design, where building façades function not only as protective elements but also as visual communication media that shape brand identity. This study aims to identify the typology of façade elements and compositions that define the architectural character of coffee shops in the area. Using a qualitative descriptive approach, data were collected through field observation, visual documentation, and measurements on eleven selected coffee shop buildings. The findings reveal that flat roofs, brick and concrete walls with painted finishes, wooden and metal cladding, large glass windows with aluminum or wooden frames, and sun-shading elements such as canopies and ventilation blocks (rosters) are the most commonly used features. In terms of composition, façades display variations of dynamic rhythms and asymmetrical balance, dominated by neutral color palettes. These combinations of elements and compositions contribute to the creation of a strong visual identity, appealing particularly to the younger generation and supporting effective branding strategies. This research contributes to a deeper understanding of contextual, communicative, and aesthetic commercial façade design and serves as a practical reference for architects and business owners in designing competitive and visually engaging buildings.